2002
DOI: 10.1029/2001jd000355
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of drop size distribution in the southwestern Amazon basin

Abstract: Simultaneous observations of an optical and an impact type disdrometer and their application in radar rainfall estimation are evaluated. The disdrometers and two collocated rain gauges were operated in the southwest Amazon region of Brazil in 1999 as part of a NASA Tropical Rainfall Measuring Mission (TRMM) field campaign and the hydro‐meteorological component of the Large Scale Biosphere–Atmosphere Experiment (LBA). During the experiment, we observed large drops with diameters greater than 5 mm. These large d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
4

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 39 publications
5
37
0
4
Order By: Relevance
“…As shown in Figures 1(a) and (b), at Gadanki the wind flow in the SW monsoon is over the continent, while in the NE monsoon it is over the ocean (Bay of Bengal). Therefore, the rainfall and DSD are mostly continental and oceanic in nature during SW and NE monsoon seasons, respectively, consistent with the observations of Kozu et al (2006) (Tokay et al, 2002;Rosenfeld and Ulbrich, 2003;Bringi et al, 2003;Ulbrich and Atlas, 2007). For instance, during moderate to heavy rain (R > 10 mm hr −1 ), 80% of the D m population at Gadanki is in the range 1.5-2.6 and 1.3-2.2 mm in the SW and NE monsoons, respectively.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…As shown in Figures 1(a) and (b), at Gadanki the wind flow in the SW monsoon is over the continent, while in the NE monsoon it is over the ocean (Bay of Bengal). Therefore, the rainfall and DSD are mostly continental and oceanic in nature during SW and NE monsoon seasons, respectively, consistent with the observations of Kozu et al (2006) (Tokay et al, 2002;Rosenfeld and Ulbrich, 2003;Bringi et al, 2003;Ulbrich and Atlas, 2007). For instance, during moderate to heavy rain (R > 10 mm hr −1 ), 80% of the D m population at Gadanki is in the range 1.5-2.6 and 1.3-2.2 mm in the SW and NE monsoons, respectively.…”
Section: Discussionsupporting
confidence: 72%
“…Except for the first study mentioned above, all other studies used ensembles of rain DSDs collected from several geographical locations with an assumption that all oceanic (continental) DSD are influenced by similar microphysical processes. The study by Tokay et al (2002), similar to the present study, has shown that the DSD at a single location can be influenced by both oceanic and continental precipitating systems. Nevertheless, the range of D m or D 0 values in all these studies is nearly equal.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…An impact type Joss-Waldvogel (Joss and Waldvogel 1967) ; b=0.9926, and c = -0.5138) with Z H in mm 6 m -3 , Z DR in dB, and K DP in deg km -1 . The polarimetric radar parameters of Z H , Z DR , and K DP , were calculated for each minute of DSD observations for an S-band radar (10.7 cm) and a temperature of 20 ˚C as shown in Tokay et al (2002). For drop shape, the mean axis ratios offered by Andsager et al (1999) were adopted for drops less than 4 mm in diameter and equilibrium drop shapes (Beard and Chuang 1987) for larger drops.…”
Section: Methodsmentioning
confidence: 99%
“…Marshall and Palmer, 1948, Joss and Waldvogel, 1968, Lakomá, 1971, Federer and Waldvogel, 1975, Li and Zhang, 1980 or more recently (e.g. Doelling et al, 1996, Hubert et al, 1999, Tokay et al, 1999, Tokay et al, 2002, Schönhuber et al, 2000, Bringi et al,2003 using different types of measurement technique (filter or glass catchment, electromechanical distrometer, optical distrometer, videodistrometer and others). Many DSD measurements have been made by the electromechanical distrometer the concept of which was developed by Joss and Waldvogel (e.g.…”
Section: Dsd Measurementmentioning
confidence: 99%